2016
DOI: 10.18632/oncotarget.13207
|View full text |Cite
|
Sign up to set email alerts
|

Immunoscore encompassing CD3+ and CD8+ T cell densities in distant metastasis is a robust prognostic marker for advanced colorectal cancer

Abstract: Background: The immunoscore (IS), an index based on the density of CD3+ and CD8 + tumor-infiltrating lymphocytes (TILs) in the tumor center (CT) and invasive margin (IM), has gained considerable attention as a prognostic marker. Tumorassociated macrophages (TAMs) have also been reported to have prognostic value. However, its clinical significance has not been fully clarified in patients with advanced CRC who present with distant metastases.Methods: The density of CD3 + , CD4 + , CD8 + , FOXP3 + , CD68 + , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 39 publications
5
105
0
3
Order By: Relevance
“…After revision, 16 of these 24 papers were excluded for following reasons: eight studies did not provide HRs or CIs, seven studies were reviews, and one study was case report. Therefore, eight studies fulfilled our eligibility criteria for the analysis . Among them, one paper reported the results of two different population respectively, so it was treated as two studies for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After revision, 16 of these 24 papers were excluded for following reasons: eight studies did not provide HRs or CIs, seven studies were reviews, and one study was case report. Therefore, eight studies fulfilled our eligibility criteria for the analysis . Among them, one paper reported the results of two different population respectively, so it was treated as two studies for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, eight studies fulfilled our eligibility criteria for the analysis. 11,[21][22][23][24][25][26][27] Among them, one paper 24 reported the results of two different population respectively, so it was treated as two studies for analysis. Table 1 presented the characteristics of the eight included studies.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in part 2 of this review, TILs in melanoma metastases have been shown to have similar prognostic importance to those in the primary lesion [103–106]. TILs in liver and lung metastases of colorectal carcinoma also show prognostic significance [107109]. An interesting observation comparing primary breast tumors and later in-breast relapses, based on a very small cohort, is that higher levels of TILs may be associated with true recurrence type relapses while new primary type relapses show lower TIL levels [110].…”
Section: Tils In the Metastatic Settingmentioning
confidence: 99%
“…In particular, diverse types of tumor‐infiltrating lymphocytes (TILs) produced different effects on tumor growth, recurrence, and metastatic spreading . Accumulating evidence has shown that the presence of TILs is significantly correlated with prognosis of various solid tumors, such as head neck squamous cell carcinoma (HNSCC), gastric cancer, colorectal cancer, breast cancer, and non‐small cell lung cancer . Currently, the most common markers for TILs are CD3 and CD8 which label pan‐T and cytotoxic T cells, respectively.…”
Section: Introductionmentioning
confidence: 99%